Analisis Pengaruh Komposisi Material Baglog Terhadap Pertumbuhan Jamur Tiram Menggunakan Metode Taguchi - I Nengah Yoga Dwiguntanu; Nur Islahudin; Tegar Theo Jodanta; Ishar Khoir Udin; Dony Satriyo Nugroho (President University, 2022)
Baglog is a growing medium for oyster mushrooms by mixing several ingredients. This study aims to determine the effect of the composition dose on fungal growth. This study uses an experimental design with the Taguchi method to determine the internal factors that influence the composition of the baglog. The Taguchi method is a method of engineering for improving products that can be done quickly and requires low costs but produces high-quality products. In the experimental design, the Taguchi method reduces the effects of the causal factors without eliminating them. The experiment is to find the most significant value from the calculation results of the Taguchi method is Larger to the better. The results of the experiments show the highest value based on the calculation. Bigger is better, namely 250ml of water, 70gr of bran, 2 minutes of stirring time, and clockwise stirring technique.